ISLAM DAN GLOBALISASI - Musthofa Ibrahim; Nala Hanifatul Magfiroh; Putri Aulia Nurrizki Fadillah (Melati Institute, 2023)
In this time of globalization, any information pertinent to current affairs (contemporary issues) is worth examining. in this paper, the reviewer will present the facts that occur with social change (globalization). influence in the social system, this situation must be faced wisely. Islam is a universal religion. therefore, Islam has a great influence on social change (globalization). with this change (globalization) there will certainly be positive and negative impacts. However, Muslims must be smart and wise to go towards globalization. Moderation in the face of various attacks of understanding and opinion. describes the attitude that must be shown by a Muslim. This study is motivated by many polemics circulating in the midst of the phenomenon of globalization, so this study is present to briefly discuss the polemics of globalization, the formulation of the problem in this study is how to position Islam in the global arena? Then the purpose of this study is to respond to the position of Islam that has entered the global world stage through a descriptive qualitative approach. Islam is a perfect religion, which is timeless and will always exist and be the right solution to handle the challenges of the times, especially in the era of globalization. The presence of globalization in the Islamic world has a positive impact, namely with its technological advances we can access everything, especially knowledge more easily, while the negative impact is the erosion of morals, morals, and lifestyles of a Muslim unconsciously due to the influence of western culture carried by globalization. The existence of globalization in the Islamic world is the center of attention that has been discussed until now, the difference in basic foundations is the cause of friction between them, so how should a Muslim respond to this? As a Muslim, can we follow globalization policies that are not in accordance with Islamic principles, if so, how? These are some of the questions that, insha Allah, we will discuss this time.